2016
DOI: 10.15761/pccm.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis with Polyangiitis (GPA) Case Report Outlining the Importance of Urinalysis in Patients Presenting with Pulmonary Cavitary Lesions

Abstract: Zagelbaum N (2016) Granulomatosis with polyangiitis (GPA) case report outlining the importance of urinalysis in patients presenting with pulmonary cavitary lesions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Glomerulonephritis is the most common renal pathology affecting 70-85% of people with GPA but only 10-15% of patients present with severe renal inadequacy with creatinine over 2 mg/dL [ 6 ]. Though over 70% of patients can present with renal symptoms, usually this takes over two years to develop [ 7 ]. Our patient’s disease rapidly progressed, and he had a need for dialysis within days of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerulonephritis is the most common renal pathology affecting 70-85% of people with GPA but only 10-15% of patients present with severe renal inadequacy with creatinine over 2 mg/dL [ 6 ]. Though over 70% of patients can present with renal symptoms, usually this takes over two years to develop [ 7 ]. Our patient’s disease rapidly progressed, and he had a need for dialysis within days of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 As per previous reports, later on we decided to add plasmapheresis with existing regimen to quickly decrease the load of pathogenic ANCA. 9,14,15 As on date, no much clinical data and large multi-modal trials are present to support the treatment. However, some studies suggested that utilisation of this plasmapheresis in severe renal failure scenarios have showed a reduction of dialysis from 60% to 40% post 1 year followed by treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies suggested that utilisation of this plasmapheresis in severe renal failure scenarios have showed a reduction of dialysis from 60% to 40% post 1 year followed by treatment. 14,16 To keep symptoms under control and to avoid relapse, rituximab was introduced to the existing pulse steroids regimen. Rituximab (2 doses) has showed some positive results by clearing the circulating B cells from the circulation and by targeting the CD20 antigen on B cells, without affecting plasma cells which may be important in disease relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation